Are babies conceived during Ramadan born smaller and sooner than babies conceived at other times of the year? A Born in Bradford Cohort Study - Daley, A; Pallan, M; Clifford, S; Jolly, K; Bryant, M; Adab, P; Cheng, KK; Roalfe, A (BMJ Publishing Group, 2017)
It is not known whether infants exposed to intermittent maternal fasting at conception are born smaller or have a higher risk of premature birth than those who are not. Doctors are therefore unsure about what advice to give women about the safety of Ramadan fasting. This cohort study aimed to investigate these questions in Muslim mother-infant pairs to inform prenatal care.Routinely collected data accessed from maternity records were the source for information. Mothers were considered exposed if they were Muslim and Ramadan overlapped with their infant conception date, estimated to be 14 days after the last menstrual period. Infants were included as exposed if their estimated conception date was in the first 21 days of Ramadan or 7 days prior to Ramadan.After adjusting for gestational age, maternal age, infant gender, maternal body mass index at booking, smoking status, gestational diabetes, parity and year of birth, there was no significant difference in birth weight between infants born to Muslim mothers who were conceived during Ramadan (n=479) and those who were not (n=4677) (adjusted mean difference =24.3 g, 95% CI -16.4 to 64.9). There was no difference in rates of premature births in exposed and unexposed women (5.2% vs 4.9%; OR=1.08, 95% CI 0.71 to 1.65).Healthy Muslim women considering becoming pregnant prior to, or during Ramadan, can be advised that fasting does not seem to have a detrimental effect on the size (weight) of their baby and it appears not to increase the likelihood of giving birth prematurely.